Dissecting the Genetics of Early Vigour to Design Drought-Adapted Wheat - Vukasovic, Stjepan; Alahmad, Samir; Christopher, Jack; Snowdon, Rod J.; Stahl, Andreas; Hickey, Lee T. (Frontiers in Plant Science, 2022)
Due to climate change and an increased frequency of drought, it is of enormous importance to identify and develop traits that result in adaptation and improvement of crop yield stability in drought-prone regions with low rainfall. Early vigour, defined as the rapid development of leaf area in early development stages, is reported to contribute to stronger plant vitality, which can in turn enhance resilience to erratic drought periods. Furthermore, early vigour improves weed competitiveness and nutrient uptake. Here, two sets of a multi-parent nested association mapping (MR-NAM) population of bread wheat (Triticum aestivum ssp. aestivum L.) were used to investigate early vigour in a rainfed field environment for three years and additionally tested under controlled conditions in a greenhouse experiment. The normalised difference vegetation index (NDVI) calculated from red/infrared light reflectance was used to quantify early vigour in the field, revealing a correlation (p < 0.05) between the spectral measurement and the leaf length of the second leaf. Under controlled environmental conditions, the projected leaf area measured using a green-pixel counter was also correlated (p < 0.05) to the leaf length of the second leaf, as well as to the recorded biomass. Subsequently, genetic determination of early vigour was tested by conducting a genome wide association study (GWAS) for the proxy traits, revealing 42 markers associated with vegetation index and two markers associated with projected leaf area. Several quantitative trait loci collocated overlapped with loci for plant developmental traits including plant height, coleoptile length, stay-green and vernalisation.